The Strategies and Projections for Energy Transition in West Java: A Policy Analysis Towards Indonesia’s Net Zero Emission (NZE) 2060 - Hasanawi, Asyrafinafilah (Universitas Dharmawangsa Medan, 2026)
This study examines the strategic policy framework for energy transition in West Java Province, Indonesia, aligned with the national Net Zero Emission (NZE) target by 2060. Through a qualitative analysis of provincial policy documents and energy modeling projections, the research outlines the revision process of the Regional General Energy Plan (RUED) in response to updated national directives. The methodology involves content analysis of the 2023 policy dialogue and energy modeling reports from the West Java Energy Office. Key findings highlight a dual strategy focusing on demand-side management through electrification and efficiency, and supply-side transformation via renewable energy maximization and decarbonization technologies such as green hydrogen, biofuels, and carbon capture. The study concludes that achieving NZE requires robust cross-sector collaboration, rational energy pricing, and significant investment in renewable infrastructure, with West Java serving as a critical regional model for Indonesia’s low-carbon transition.